Pengaruh Ekstrak Kulit Manggis (Garcinia mangostana L.) TERHADAP Testis Tikus Putih yang Diberi Paparan Gelombang Elektromagnetik Handphone - Muhartono Muhartono; Andrian Rivanda; Anggraeni Janar Wulan; Susianti Susianti (Jurnal Kesehatan, 2017)
Mobile phone electromagnetic waves will induce elevated reactive oxygen species (ROS) that may cause testicle histopathological changes. Resolving this condition, the antioxidants contained in mangosteen peel are needed. This study was to determine the effects of ethanol extract  from mangosteen peel (Garcinia mangostana L.) in order to repair testicle histopathological changes, specifically spermatozoa and spermatogenic cells on Sprague dawley strain white male rats (Rattus norvegicus) that had been exposed by handphone electromagnetic waves. This study were used 25 Sprague dawley strain white male rats with 200-300 gram body weight, then the samples were divided into 5 groups which consist of Control Group 1 (K1) with no treatments were given in rats, Control 2 (K2) were given Nacl 0,9 % and mobile phone electromagnetic waves exposures. The Treatment group (P1), (P2), and (P3) were given ethanol extract from mangosteen peel with multilevel dosage of 50, 100, 200 mg / kgBW and exposure to mobile phone electromagnetic wave for 3 hours per day along for 28 days. The result of this study showed mean of sperm cells on K1=173.75±SD 16.978, K2=101.75±7.455 SD, P1=148.50±SD 10.149, 10.247 P2=162.50± SD, P3=180.75 7.365 ± SD and mean of spermatogenic cells on K1=306.75±SD 11.955, K2= 157.00±7.303 SD, P1=243.50±SD 21.672 10.340 P2=266.75±SD P3=294.75±13.150 SD. One Way Anova test (p<0.005), sperm cells and spermatogenic cells showed significant results with p=0.000. The conclusion is ethanol extract of mangosteen peel (Garcinia mangostana L.) can repair testicle histopathological changes by inducing total  testicular sperm cells and spermatogenic cells of Sprague dawley strain white male rats (Rattus norvegicus) exposed by mobile phone electromagnetic waves.